Perancangan UI/UX E-Tracer Study UNIROW dengan Menggunakan Metode Doubel Diamond - Mellynda Oktaviana; Alfian Nurlifa; Andik Adi Suryanto; Fitroh Amaluddin (Infotek: Jurnal Informatika dan Teknologi, 2023)
Currently, at PGRI Ronggolawe Tuban University, tracer studies are still using google forms which aim to collect alumni data. It is still not effective and has many shortcomings in order to solve the problem, a UI/UX e-tracer study design was made using the double diamond method. The double diamond method is used by researchers to conduct usability evaluation tests on old tracer studies using the System Usability Scale (SUS) and the User Experience Questionnaire (UEQ). The SUS results obtained from Google's old tracer study form are 49 (grade F) while the E-Tracer Study results are 82.6 (grade B) and the results from the UEQ show an attractiveness scale from 0.41 to 2.04, pepisicuity scale 0.21 to 2.28, efficiency scale 0.23 to 2.18, dependability scale 0.51 to 1.80, stimulation scale 0.54 to 2.13, and novelty scale -0.09 to 1.88. This proves that UI/UX design in E-Tracer Study resulted in an increase in usability